Intrafloral patterns of color and scent in Capparis spinosa L. and the ghosts of its selection past. Issue 1 (15th December 2022) - Kantsa, Aphrodite; Garcia, Jair E.; Raguso, Robert A.; Dyer, Adrian G.; Steen, Ronny; Tscheulin, Thomas; Petanidou, Theodora
Abstract: Premise: Capparis spinosa is a widespread charismatic plant, in which the nocturnal floral habit contrasts with the high visitation by diurnal bees and the pronounced scarcity of hawkmoths. To resolve this discrepancy and elucidate floral evolution of C. spinosa, we analyzed the intrafloral patterns of visual and olfactory cues in relation to the known sensory biases of the different visitor guilds (bees, butterflies, and hawkmoths). Methods: We measured the intrafloral variation of scent, reflectance spectra, and colorimetric properties according to three guilds of known visitors of C. spinosa . Additionally, we sampled visitation rates using a motion‐activated camera. Results: Carpenter bees visited the flowers eight times more frequently than nocturnal hawkmoths, at dusk and in the following morning. Yet, the floral headspace of C. spinosa contained a typical sphingophilous scent with high emission rates of certain monoterpenes and amino‐acid derived compounds. Visual cues included a special case of multisensory nectar guide and color patterns conspicuous to the visual systems of both hawkmoths and bees. Conclusions: The intrafloral patterns of sensory stimuli suggest that hawkmoths have exerted strong historical selection on C. spinosa . Our study revealed two interesting paradoxes: (a) the flowers phenotypically biased towards the more inconsistent pollinator; and (b) floral display demands an abundance of resources that seems maladaptive in the habitats of C. spinosa . The transition to a binary pollination system accommodating large bees has not required phenotypic changes, owing to specific eco‐physiological adaptations, unrelated to pollination, which make this plant an unusual case in pollination ecology.